#GivingTuesday 2018 hits record $380 million mark. Issue 353 (17th January 2019) - Unknown
Abstract : Fundraising totals from #GivingTuesday 2018 hit record highs, according to preliminary calculations, with U.S.‐based individuals, civic coalitions, nonprofit organizations, schools and businesses bringing in over $380 million in online donations to benefit a broad range of causes.